MOLECULAR MODELLING OF Mn+.[DBz16C5] COMPLEXES, M = Li+, Na+ AND Zn2+ BASED ON MNDO/d SEMIEMPIRICAL METHOD - Harno Dwi Pranowo; Chairil Anwar (Universitas Gadjah Mada, 2006)
The effect of substituent on dibenzo-16-crown-5 (DBz16C5) and interaction between these crown ether with metal cations was evaluated using computational chemistry calculations. Substituens where are connected to the benzene ring on the DBz16C5 are -COOH, -Br, -COOC2H5, -CHO, -CH=CHCO2H, -CH=CHCO2C2H5 and -CH(OH)CH3. The analysis based on computational chemistry calculation using MNDO/d semi empirical method was done. The first step is structure optimization of crown ether followed by optimization of crown ether-metals cation complexes Mn+.[DBz16C5], where M is Li+, Na+ and Zn2+. Interactions of the crown ether and cation were discussed in term of the structure parameter of crown ether, atomic charges and energy interaction of the crown ether-metals cation. Electron donating groups increase the capability of crown ether to bind cation by means of induction effect, while electron withdrawing groups reduce the ability of crown ether to bind cation. Any substituent on the benzene in DBz16C5 which can be make the symmetrical form of the crown ether-metals cation complexes will increase the selectivity of the crown ether to bind the cation. Selectivity of the crown ether to bind cation also depends on the compatibility of the diameter of cation and cavity of crown ether. DBz16C5 has higher selectivity to bind the Na+ compare to the Li+ and Zn2+.